Pengaruh Budaya Organisasi dan Lingkungan Kerja terhadap Motivasi Kerja Pegawai Badan Penelitian dan Pengembangan Daerah Provinsi Kalimantan Timur - Susanto, Muhammad Erlangga Dewa; Kusumawati, Yulia Tri; Saputra, Praja Hadi (Innovative: Journal Of Social Science Research, 2025)
This study aims to analyze the influence of organizational culture and work environment on employee work motivation at the Regional Research and Development Agency (Balitbangda) of East Kalimantan Province. Work motivation is an essential factor that drives individuals to perform their tasks optimally. A decline in motivation within Balitbangda is indicated by low employee initiative and tardiness, which are suspected to be influenced by a weak organizational culture and an unsupportive work environment. This research uses a quantitative approach with a population of 67 employees and a saturated sample of 60 respondents. Data collection techniques include questionnaires and interviews, and the data are analyzed using multiple linear regression. The results show that organizational culture and work environment, both partially and simultaneously, have a significant effect on work motivation. An adaptive and participative organizational culture, as well as a comfortable, safe, and conducive work environment, can enhance employees’ enthusiasm and engagement in carrying out their duties. The coefficient of determination of 53.8% indicates that more than half of the variation in work motivation is explained by these two variables. The practical implication of this study is the importance of leadership attention to strengthening work culture values and improving workplace facilities and comfort to support employee productivity and well-being. These findings provide theoretical contributions to the field of human resource management and can serve as a policy reference for improving the performance of government agencies.